AB0179 Mesenchymal Stem Cells Promote the Generation of CD206+ Macrophage and Increase its Phagocytic Activity in Systemic Lupus Erythematosus. (9th June 2015) - Deng, W.; Chen, W.; Zhang, Z.; Huang, S.; Kong, W.; Sun, Y.; Feng, X.; Tang, X.; Yao, G.; Sun, L.
Abstract : Background: Umbilical cord (UC)-derived mesenchymal stem cells (MSCs) have been confirmed to exert therapeutic effects on systemic lupus erythematosus (SLE). Deficiency in SLE macrophages exhibits excessive activation and inefficient clearance of self nuclear antigens. However, whether the benefit effect of UCMSCs on SLE was mediated by regulatory effects on macrophages remains to be elucidated. Objectives: We aim to explore whether UCMSCs could educate SLE macrophage to become a kind of alternatively activated macrophage and increase its phagocytic activity. Methods: UCMSCs were injected into B6.MRL- Fas lpr mice. The therapeutic effects of MSCs transplantation were evaluated by the renal pathology, proteinuria, spleen index, T lymphocyte subpopulation and plasma cells. Murine peritoneal/renal macrophages were isolated to detect the proportion of alternatively activated macrophage (F4/80 + CD206 + ). To determine the phagocytic activity of murine peritoneal/renal macrophages, FITC-labeled flurospheres were added into the cultures. The uptake of FITC-labeled flurospheres was determined by flow cytometry. CD14 + monocytes were isolated from peripheral blood of healthy donors (HC) and SLE patients. We cultured human monocytes for 7 days with macrophage colony-stimulating factor (M-CSF) to generate macrophages, and then cocultured them for 2 more days with UCMSCs in a transwell culture system. The levels of CD206 and phagocytic activity of macrophages were detected by flow cytometry. Results: Compared with C57BL/6 mice, B6.MRL- Fas lpr mice macrophages exhibited lower level of CD206, the marker of alternatively activated macrophages. In addition, the phagocytic activity of B6.MRL- Fas lpr mice macrophages was also decreased. UCMSCs transplantation could rescue both the proportion of CD206 + macrophages and the phagocytic activity. Interestingly, the proportion of CD206 + macrophages was positively correlated with the phagocytic activity. Similar to the lupus mice, macrophages from SLE patients showed lower expression of CD206 and phagocytic activity. SLE macrophages cocultured with UCMSCs consistently increased the expression of CD206 and phagocytic activity. In addition, the up-regulation of phagocytic activity by UCMSCs was only appeared in CD206 + macrophages. This phenomenon was also observed in UCMSCs transplanted SLE patients. Furthermore, the addition of specific neutralizing antibodies/inhibitor/siRNA of HGF, TGFβ1, PGE2 and HO-1 could not reverse the effects of UCMSCs on SLE macrophages. Conclusions: UCMSCs could alleviate SLE through promoting the generation of CD206 + macrophage and increasing its phagocytic activity, and these effects was independent of HGF, TGFβ1, PGE2 and HO-1. Disclosure of Interest: None declared